Study Of Talling Compatibility To Production Palm Oil (Elaeis guineensis Jacq) In PT. Langkat Nusantara Kepong Tanjung Beringin Garden Hinai District, Langkat Regency. - Arie Hapsani Hasan Basri; Herjono Tampubolon; Aisar Novita (Jurnal Online Pertanian Tropik, 2023)
Study of Talling Suitability for Palm Oil (Elaeis guineensis Jacq) Production at PT. Langkat Nusantara Kepong Tanjung Beringin Gardens. The purpose of this study was to examine the percentage of suitability of talling with production and to examine the factors that affect the suitability of talling with oil palm production at PT. Langkat Nusantara Kepong Tanjung Beringin Gardens. This assessment was carried out from March to June 2022. The data collection method was carried out by means of interviews with garden assistants and harvest foreman and secondary data was obtained from the division office. The statistical analysis used was a simple statistical analysis using tables and diagrams using a one sample t-test which is used to compare the difference in the percentage of talling with the production to be compared with company standards. The results showed that the talling calculation was not accurate with the realization of production with a percentage of 91.67%. The factors that affect the suitability of talling with the realization of production were the accuracy of talling calculations, rainfall, fruit loss in the field and the number of harvesters with their work performance.